Biological Processes that Prepare Mammalian Spermatozoa to Interact with an Egg and Fertilize It - Daulat R. P. Tulsiani; Aïda Abou-Haila (Scientifica)
In the mouse and other mammals studied, including man, ejaculated spermatozoa cannot immediately fertilize an egg. They require a certain period of residence in the female genital tract to become functionally competent cells. As spermatozoa traverse through the female genital tract, they undergo multiple biochemical and physiological changes collectively referred to as capacitation. Only capacitated spermatozoa interact with the extracellular egg coat, the zona pellucida. The tight irreversible binding of the opposite gametes triggers a Ca2+-dependent signal transduction cascade. The net result is the fusion of the sperm plasma membrane and the underlying outer acrosomal membrane at multiple sites that causes the release of acrosomal contents at the site of sperm-egg adhesion. The hydrolytic action of the acrosomal enzymes released, along with the hyperactivated beat pattern of the bound spermatozoon, is important factor that directs the sperm to penetrate the egg coat and fertilize the egg. The sperm capacitation and the induction of the acrosomal reaction are Ca2+-dependent signaling events that have been of wide interest to reproductive biologists for over half a century. In this paper, we intend to discuss data from this and other laboratories that highlight the biological processes which prepare spermatozoa to interact with an egg and fertilize it.